2001
DOI: 10.1046/j.1466-7657.2001.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing informatics: yesterday, today and tomorrow

Abstract: Today, at the beginning of the 21st century, nursing informatics has become a part of our professional activities. Informatics has advanced the field of nursing by bridging the gap from nursing as an art to nursing as a science. This article discusses the major milestones that have influenced the growth of computer technology and the specific efforts that have influenced yesterday's creation of the nursing informatics movement. It also provides an overview of nursing informatics in today's health care industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Saba suggested that computer technology plays a significant role in professional nursing practices and will shape the future of nursing. Sherwood stated that health‐care information systems will contribute to the planning of evidence‐based nursing and treatment practice strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Saba suggested that computer technology plays a significant role in professional nursing practices and will shape the future of nursing. Sherwood stated that health‐care information systems will contribute to the planning of evidence‐based nursing and treatment practice strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Saba [7] discussed the future of nursing and suggested that computer technology must be part of the professional nursing practice. McNeil et al went on to specifically define the needed computer literacy skills as; word processing, databases, spreadsheets and email.…”
Section:  Human Computer and Human Information Interactionmentioning
confidence: 99%
“…It is first essential to define the term informatics because of its criticality to the development of the five core areas for healthcare professionals and because general awareness of what informatics entails remains elusive (16) . The term informatics was derived from the French term informatique , which refers to " the computer milieu " (17) . Its use can be traced to a Russian document published in 1968 (18) .…”
Section: Current Status Of Informatics Education In the Healthcare Prmentioning
confidence: 99%